Avaliação de fontes de amônia para o tratamento de fenos de gramíneas tropicais. 2. Compostos nitrogenados - Reis, Ricardo Andrade [UNESP]; Rodrigues, Luis Roberto de Andrade [UNESP]; Resende, Kleber Tomás de [UNESP]; Pereira, João Ricardo Alves; Ruggieri, Ana Cláudia (Sociedade Brasileira de Zootecnia, 2001)
Este estudo foi desenvolvido para se avaliarem as alterações nos conteúdos de compostos nitrogenados dos fenos de braquiária decumbens (Brachiaria decumbnes Stapf) e jaraguá (Hyparrhenia rufa Ness Stapf) não-tratados, tratados com uréia (U - 5,4% da MS), uréia (UL - 5,4% da MS) mais labe-labe (Lablab purpureus L. Sweet, cv. Highworth-3,0% da MS) ou amônia anidra (NH3 -3,0% da MS). A aplicação de amônia anidra ou de uréia aumentou os teores de N total, N insolúvel em detergente neutro, N insolúvel em detergente ácido, N não-protéico e N amoniacal. A amonização diminuiu as relações N insolúvel em detergente neutro/N total e N insolúvel em detergente ácido/N total e aumentou as relações N não-protéico/N total, N amoniacal/N total e os teores de PB. O N aplicado foi retido, principalmente, nas formas de NNP e N amoniacal.

The experiment was conducted to evaluate the changes on the nitrogen compounds of the Brachiaria decumbens Stapf, jaraguá (Hyparrhenia rufa Ness Stapf) grasses hay, untreated, treated with urea (5.4% DM), urea plus lab-lab (UL-5.4% DM plus Lablab purpureus L. Sweet, cv. Highworth-3.0% DM) and anhydrous ammonia (NH3 - 3.0% DM). The chemical treatment with urea or NH3 increased the total N, neutral detergent insoluble N 9NDIN), acid detergent insoluble N (ADIN), non nitrogen protein (NNP), and the ammonical nitrogen (AN) contents. Ammoniation decreased the NDIN/TN and ADIN/TN ratios. The chemical treatment increased the NNP/TN and NA/TN ratios, and the crude protein contents. The N applied as urea or NH3 was retained as NNP and in the ammoniacal form.
Evaluation of ammonia sources to tropical grasses hays treatment. 2. Nitrogen compounds
Keywords: ammoniation; Chemical composition; nitrogen compounds; tropical grass; Urea; Amonização; amônia anidra; Composto nitrogenado; gramíneas tropicais; Nitrogênio amoniacal; Uréia